Clinical outcomes of late decompression surgery following cervical spinal cord injury with pre-existing cord compression. Issue 4 (April 2018) - Konomi, Tsunehiko; Yasuda, Akimasa; Fujiyoshi, Kanehiro; Yamane, Junichi; Kaneko, Shinjiro; Komiyama, Takatsugu; Takemitsu, Masakazu; Yato, Yoshiyuki; Tsuji, Osahiko; Matsumoto, Morio; Nakamura, Masaya; Asazuma, Takashi
Abstract Study design Retrospective cohort study. Objectives The purpose of the current study was to examine the effectiveness of late decompression surgery for traumatic cervical spinal cord injury (CSCI) with pre-existing cord compression. Setting Murayama Medical Center, National Hospital Organization, Tokyo, Japan. Methods In total 78 patients with traumatic CSCI without bone injury hospitalized in 2012–2015 in our institute for rehabilitation after initial emergency care were divided into four groups according to the compression rate (CR) of the injured level and whether or not decompression surgery was performed. Neurological status was evaluated by American Spinal Injury Association impairment scale (AIS), Barthel index, and Spinal Cord Independence Measure (SCIM). Results In the severe compression group (CR ≥ 40%), >2 grade improvement in the AIS was observed in 30% of patients with surgical treatment, although it was not observed in any patient without surgery. The SCIM improvement rate at discharge was 60% in the surgical treatment group and 20% in the non-surgical treatment group. In the minor compression group (CR < 40%), >2 grade improvement in the AIS was observed in 18% of patients with surgical treatment and in 11% without surgery. The SCIM improvement rate at discharge was 52% in the surgical treatment group and 43% in the non-surgical treatment group. Conclusions These results indicate that surgical treatment has an advantage for patients following traumatic CSCI with severe cord compression. In contrast, surgical efficacy is not proved for CSCI patients without severe cord compression.